Nyabis tradition in Madura: A meta-ethnographic study - Arina Mufrihah; Ilfiandra Ilfiandra; Nandang Budiman (Universitas Muhammadiyah Malang, 2025)
Nyabis is one of the pesantren (Islamic boarding school) traditions in Madura which depicts the essence of the relationship between students and teachers. Unfortunately, there are no previous articles that discuss the meaning and concept of nyabis comprehensively. This article aims to synthesize previous literature on nyabis with interpretive methods and critical examination to construct an integrate concept of nyabis in Madura through meta-ethnographic methods. The meta-ethnographic method with seven stages of meta-synthesis produces the concept of nyabis which consists of the definition, purpose, and context of nyabis; the values and figures in; the scope and the orientation of nyabis. Nyabis is a tradition of visiting Kiai (ulama) in Islamic boarding schools carried out by students and the community to fulfill short-term goals, namely problem solving and decision making; and the long-term goal, namely gaining religious knowledge as a foundation for a blessed life in this world and the hereafter. Kiai have various roles including educators, mentors and spiritual teachers to meet the needs of people's lives in the scope or personal, social, educational, economic and spiritual aspects. Nyabis merupakan salah satu tradisi pesantren di Madura yang menggambarkan tentang kelestarian esensi hubungan antara murid dan guru. Sayangnya, belum ada artikel terdahulu yang membahas makna dan konsepnya secara utuh. Artikel ini bertujuan mensintesis literatur terdahulu tentang nyabis dengan metode interpretatif dan pemeriksaan kritis untuk mengonstruk konsep utuh nyabis di Madura melalui metode meta-etnografi. Metode meta-etnografi dengan tujuh tahapan meta-sintesis menghasilkan konsep utuh tentang nyabis. Nyabis adalah tradisi silaturahmi kepada Kiai (ulama) di pondok pesantren yang dilakukan oleh santri maupun masyarakat untuk memenuhi tujuan jangka pendek, yaitu pemecahan masalah dan pengambilan keputusan; dan tujuan jangka panjang, yaitu memperoleh ilmu agama sebagai landasan bagi kehidupan yang berkah di dunia dan akhirat. Kiai memiliki peran beragam meliputi pendidik, pembimbing, dan guru spiritual untuk memenuhi kebutuhan hidup masyarakat dalam ruang lingkup atau aspek personal, sosial, pendidikan, ekonomi, dan spiritual.